Planning loads of different intensity in the annual cycle of training highly qualified cyclists in the aspect of foreign research - Pogrebnoy A.I. ,; Komlev I.O. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identification of modern approaches to planning loads of different intensity in the annual training cycle of highly qualified cyclists. Methods and structure of the study. Analysis of literary sources. More than 50 sources of foreign literature published in recent years were analyzed. Results and conclusions. In the four load distribution options described in foreign publications (polarization, pyramidal, threshold and high-intensity models), the effectiveness of both the polarized and pyramidal options is noted. At the same time, the most important area of ​​training activity is the use of large volumes of low-intensity training. In addition, it is also recommended to use short, moderate-intensity and high-intensity training sessions consistent with competition intensity. Optimizing training load prior to a major event using a compressed version of high-intensity overload training followed by a taper period provides improved performance levels in elite cyclists compared to traditional taper training.